Customer Satisfaction Based on Store Atmosphere and Service Quality at Toko SRC Dede Majalengka - Anna Siti Hasanah; Ahmad Kamaludin; Gita Kartika Sari; Imma Ismaniar (Politeknik Mardira Indonesia, 2025)
This study aims to examine the influence of store atmosphere and service quality on consumer satisfaction at Toko SRC Dede in Cikasarung Village, Majalengka Regency. With the rapid growth of retail businesses, it is essential for retailers to create a comfortable and engaging shopping experience. The research method employed is quantitative, with data collected through questionnaires distributed to 100 respondents. Then the data was annalyzed using SPSS 25.0 version and Microsoft Excel including validity test, realibility test, normality test, regression analysis, hypothesis testing which include one sample t-test, t test, and F test, and last is analysis of coefficient determination. The result of this research show that: (1) store atmosphere has a positive and significant effect on consumer satisfaction, (2) product quality has a positive and significant effect on consumer satisfaction, (3) simultaneously store atmosphere and product quality have a positive and significant effect on consumer satisfaction. The conclusion of this study is that both store atmosphere and service quality significantly influence consumer satisfaction at Toko SRC Dede, which is expected to provide insights for management to continuously enhance the customer shopping experience.